Model spiritual care with an adaptation theory approach Callista Roy on cortisol levels - Kusuma, Aria Nurahman Hendra; Pudjonarko, Dwi; Sujianto, Untung; Susanto, Hardhono; Ibrahim, Kusman; Dwidiyanti, Meidiana (Universitas 'Aisyiyah Yogyakarta, 2025)
Ischemic stroke is a cause of physical disability. These defects result in impaired biopsychosociospiritual adaptation in stroke patients. The inability to adapt will cause an anxiety reaction which triggers an increase in cortisol levels. The spiritual care model helps patients find meaning and purpose in life as well as an optimistic attitude so that they have better adaptability. This type of research is Quasy Experimental with a pretest-posttest control group design. The study population was ischemic stroke patients in the Outpatient Department of Dr. Regional General Hospital. Moewardi Surakarta. The total sample consisted of 60 respondents, divided into 30 control group respondents and 30 intervention group respondents, who received a spiritual care model intervention in the outpatient room of Dr RSUD. Moewardi Surakarta. The research results show the influence of the Spiritual Care Model Using Callista Roy's Adaptation Theory Approach on Cortisol Levels in Ischemic Stroke Sufferers with a significance value of 0.043 < 0.05. The Spiritual care model influences the amygdala, which stimulates the hypothalamus through the hypothalamic-pituitary-adrenal (HPA) axis, thereby inhibiting the excretion of corticotropin-releasing factor (CRF). The pituitary gland then stimulates adrenocorticotropic hormone (ACTH), which reduces cortisol. This research has a contribution that spiritual care interventions can improve the adaptability of biopsychosocial rehabilitation of stroke patients. This research has a contribution that spiritual care interventions can improve the ability to adapt biopsychosocial rehabilitation of stroke patients.